New Bipolar Hybrid Carrier PWM Strategies for Symmetrical Multilevel Inverter - C.R. Balamurugan; S.P. Natarajan; R. Bensraj (Institute of Advanced Engineering and Science, 2015)
In this paper, hybrid modulation methods suitable for H-bridge MLI are discussed. The results of experimental work using dSPACE system only are presented for three phase five level cascaded type inverter. Different hybrid carrier PWM (Pulse Width Modulation) strategies using sinusoidal reference, third harmonic injection reference, 60 degree reference and stepped wave reference for the chosen inverter are initially developed using SIMULINK. Strategies developed are then implemented in real time using dSPACE/RTI. The five level output voltages of the chosen MLI (MultiLevel Inverter) obtained using the dSPACE system based PWM strategies and the corresponding % THD (Total Harmonic Distortion) and VRMS (fundamental) are presented and analyzed. It is seen that sinusoidal reference with PS+VF (Phase shift+Variable Frequency) and PS+PD (Phase Disposition) provides output with relatively low distortion. APOD+CO (Alternative Phase Dispostion+Carrier Overlapping) and CO+PD PWM strategy is found to perform better since it provides relatively higher fundamental RMS output voltage and relatively lower stress on the devices. It is displayed that THI (Third Harmonic Injection) reference with PS+VF and CO+PS provides output with relatively low distortion. APOD+CO and CO+PS PWM strategy is found to perform better since it provides relatively higher fundamental RMS output voltage and relatively lower stress on the devices. It is observed that 60 degree reference with PD+VF provides output with relatively low distortion. CO+PD PWM strategy is found to perform better since it provides relatively higher fundamental RMS output voltage and relatively lower stress on the devices. It is noted that stepped wave reference with APOD+PD and PD+VF provides output with relatively low distortion. APOD+CO and CO+PD PWM strategy is found to perform better since it provides relatively higher fundamental RMS (Root Mean Square) output voltage and relatively lower stress on the devices. The simulation and hardware results closely match with each other. DOI: http://dx.doi.org/10.11591/telkomnika.v14i2.7362